2022
DOI: 10.1039/d2ra02367a
|View full text |Cite
|
Sign up to set email alerts
|

Changing the calcination temperature to tune the microstructure and polishing properties of ceria octahedrons

Abstract: Octahedral ceria abrasives with varied microstructures were prepared by calcining a hierarchical precursor at 500–900 °C. The relationship between calcination temperature and microstructure, mechanical hardness and chemical activity was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…5 ). Similar findings were reported by Li et al 38 for ceria octahedrons where the calcination temperature decreased the zeta potential of the samples.
Figure 5 Explanation of the mechanism of zeta potential decrease with calcination temperature.
…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…5 ). Similar findings were reported by Li et al 38 for ceria octahedrons where the calcination temperature decreased the zeta potential of the samples.
Figure 5 Explanation of the mechanism of zeta potential decrease with calcination temperature.
…”
Section: Resultssupporting
confidence: 91%
“…5). Similar findings were reported by Li et al 38 for ceria octahedrons where the calcination temperature decreased the zeta potential of the samples.…”
Section: Resultssupporting
confidence: 91%
“…13 Subsequent calcination at several hundred degrees Celsius can crystalize the ceria abrasives and decompose the impurities. 14 Mechanical milling, filtration, and static settlement processes are employed to disperse the particles into uniform-sized abrasive distributions. 15,16 The control of surface Ce 3+ ratio in ceria abrasives is beneficial in improving oxide polishing.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the overall cutting effect of the abrasives, many studies have been carried out in controlling the particle size and distribution as well as morphology and surface features [10][11][12]. Several researchers prepared ceria abrasives by annealing carbonate or oxalate precursors or by calcining octahedral CeO 2 precursors self-assembled from spherical primary nanocrystals and found that the calcination temperature is also a critical parameter that governs the polishing efficiency and the quality of the polished surface [13,14]. In addition to these, Cheng et al attempted to dope a certain amount of lanthanide elements (La, Nd, and Yb) into cerium dioxide using the modified incipient impregnation method [15].…”
Section: Introductionmentioning
confidence: 99%